Ethno-cultural particularity of English, French and Russian phrasiological units with components of names of domestic animals - E. N. Belaya (Омский научный вестник: Серия "Общество. История. Современность")
The article reads about ethno-cultural particularity of English, French and Russian phraseological units (P.U.) with components of the names of domestic animals: «horse», «cow», «ass» on the basis of sources of cultural interpretation. The author of the article treats archetypes, mythologems, ritual forms of national culture, religion, literature, history. The emphasis is centred on the fact that ethnocultural particularity of P.U. with components of the names of domestic animals is caused by stereotype, symbolic character and patterning of their figurative basis. The following assertions are substantiated: 1) the figurative basis of English P.U. contains stereotyped representations of arrogant behavior of a person’s senseless activity who poses as the other person than he is in reality; of touch with Scottish realia and literature; 2) the figurative basis of French P.U. contains patterned and stereotyped representations of a person who works by the sweat of his brow, of the interaction of man and a horse, of a bad French, of a drunkard, a silly man who is fond of bombastic speech, of a cruel man; 3) the figurative basis of Russian P.U. contains stereotyped representations of a ridiculously dressed person, a pattern of human obstinacy; of touch with Russian peasant’s way of life. The conclusion is made that in these three languages universal meanings are set expressions with the components of «horse» (Trojan Horse, carthorse) and «cow» (milk cow), and that the comparative analysis of P.U. demonstrates difference in linguistic pictures of the world and sheds light on ethnic logic